An analysis of using games in learning English toward students’ vocabulary mastery in literature review - Habibie, Ainsha Ainun; Saleh, Yuwin; Friyanto, Friyanto (English Education Department, 2022)
This research study aims to investigate the effect of game mastery in learning English toward students’ vocabulary. This research employed the qualitative method. The data sources of this research are the ten international indexed journals and two national indexed journals. There are many studies about the games for learning, but those articles focus on vocabularies. This study approved that the use of games affected students’ vocabulary mastery. By using the games in learning activities, the English teachers are to facilitate the students for improving their mastering in vocabulary. There are some games that can be used to enhance vocabulary skill. They are Scattergories Game, Digital Game Based Learning, Language Games (Crowspuzzle and so on particular primary school. Then, there are Hangaroo Game, and Digital Games for intermediate students. However, this study suggests to the next researcher to analyze deeply an advantage and disadvantage of games to improve students’ vocabulary. Because this study still has many limitations to explore the games.